Kepatuhan Perpajakan UMKM Dengan Optimalisasi Data Online System (Studi Di Yogyakarta) - Yulina Alfianti Hamida; Suparna Wijaya (Politeknik Keuangan Negara STAN, 2022)
The existence of an independent tax reporting system is a gap for UMKM taxpayers in the city of Yogyakarta to report their income as little as possible. The purpose of this research is to find out whether there are differences in income reporting reported by taxpayers by self-assessment with income data recorded on the Online Transaction Monitoring (OTM) system owned by the Yogyakarta City Government. This research is a qualitative research with data collection methods through interviews and literature study. The results of the study reveal that there is a gap between mandatory income in reporting the Annual PPh PPh Final 23 of 2018 and taxpayer income recorded in the Online Transaction Monitoring (OTM) system for local tax reporting. The existence of these differences in income reporting can be used by KPP Pratama Yogyakarta to improve MSME tax compliance in the city of Yogyakarta by finding and analyzing whether there is a tax gap or not.